Noaidi drums from Sapmi, rock paintings in Finland and Sami cultural heritage:an investigation - Joy, Francis (Polar Record, 2017)
ABSTRACTA new, extensive examination of figures with horns and triangular shaped heads in prehistoric rock paintings in Finland reveals remarkable parallels with similar attributes on the Radien and Akka groups of spirits, pictured as male and female powers of the sky, earth and underworld, painted on the heads of indigenous Sami noaidi drums from Swedish and Norwegian Sapmi during the seventeenth and eighteenth centuries. What makes this particular study of interest is that the cultural context or origins of rock paintings in Finland remains ambiguous. They are contextualised as being ‘Finnish’ according to academic literature. This paper explores these theories further and presents the findings of this investigation. In light of these findings, a re-examination and re-interpretation of the cultural context of rock paintings in Finland concerning Sami pre-Christian religion and cultural heritage is prompted.